Pollen of prominent cultivated trees and wild herbaceous plant species of Tehran metropolis: an ecologic-allergic approach - Majid Beheshti; Ahmadreza Mehrabian; Farzaneh Khajoei Nasab; Mohammad Reza Fazlollahi (علوم محیطی)
Introduction: Providing a palynological database is one of the important measures in order to manage the environment of Tehran Metropolises. This database can also be used for the Pollen Atlas of Iran, pollen calendar, aerobiology, climate change, botany, the management of asthma and allergies, archaeological as well as melissopalynological studies in Tehran. Up until now, little attention has been paid to this scope, so it seems to be necessary to prepare the mentioned database. The aims of this study is to prepare SEM images of pollen grains, describe the diagnostic characteristics of pollen grains and analyze the characteristics of pollen grains in relation to allergenic properties.Material and Methods: Plant samples of this study were collected from parks and various urban green spaces as well wildlands in Tehran during 2001 to 2021. It was also deposited in the herbarium of Shahid Beheshti University (HSBU). These specimens were identified using scientific sources such as Flora of Iran, Flora Iranica, Flora of Tehran, Flora of Turkey, Flora of USSR and some illustrated guide on garden plants. Therefore, the pollen grains were photographed using Scanning Electron Microscopy (SEM). The 12-20 pollen grains of each species were evaluated using Image Tools 3.6 software to evaluate quantitative morphological traits. The terminology used to describe the pollen charactersaccording to Erdtman, Punt, and Hesse. Finally, a comprehensive description of the quantitative and qualitative morphological traits of pollen grains was prepared.Results and Discussion: In this study, pollen grains of 92 species belonging to 42 trees and herbaceous plant genera were studied. The Asteraceae with 11 species had the highest number of species in this study. The pollen grains included monad (91) and tetrad (1). Also, 70 species are isopolar and 22 species are heteropolar. Sculpturing includes 16 different types. Pollen ornamentation including 16 diverse types that reticulate, microreticulate as well peforate have the highest abundance in the studied species. The 35 plant taxa have allergenic properties based on previously published scientific studies.Conclusion: This study is the first illustrated pollen database on Tehran including 92 plant species belonging to 42 families of cultivated trees as well as wild herbs. The results of this study showed that several species have been planted regardless of their allergic effects. In addition, this study provides an important reference for allergy studies. Finally, pay attention to the planting of Non-allergenic plant species is one of the important ecological considerations in city management.